Perceived fairness and satisfaction towards performance appraisal process: Do they affect organizational commitment and industrial relations climate? - Sudin, Suhaimi; Jais, Juraifa; Mohamad, Mafuzah (2008)
Performance appraisal systems present valuable performance information to a number of critical human resource activities. Nevertheless, the performance appraisal systems impose a questionable of measurement accuracy, stimulates employee conflict and competition. Due to the paradox facets of performance appraisal system, major issues in related to an intricate dynamic relationship between employee satisfaction and perceived fairness are raised. As the employee satisfaction and perception are linked to both organizational commitment and industrial climate, it is important to gain a deeper understanding. Therefore, this paper attempts to explore the relationship between perceived fairness and reaction of performance appraisal system towards organizational commitment and industrial relations climate from an Asian perspective. Overall, this paper would be able to shed a new light in understanding the dynamic linkage, thereby leading to a new understanding of performance appraisal processes.